Photoreduction and validation of haem–ligand intermediate states in protein crystals by in situ single-crystal spectroscopy and diffraction. (2017) - Kekilli, Demet; Moreno-Chicano, Tadeo; Chaplin, Amanda K.; Horrell, Sam; Dworkowski, Florian S. N.; Worrall, Jonathan A. R.
No abstract available